(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents the assessment of the overall effect and acute toxicity level of a food supplement named "Asyetis," prepared from the aerial parts of medicinal plants such as hyssop and yarrow (bex) growing in the mountainous regions of Uzbekistan, using mice as a model for warm-blooded animals. The sample was tested at the Laboratory of Screening of Biologically Active Substances and Pharmacology at the Bioorganic Chemistry Institute named after A.S. Sodiqov of the Academy of Sciences of the Republic of Uzbekistan.